2013
DOI: 10.3109/07420528.2013.872120
|View full text |Cite
|
Sign up to set email alerts
|

Long-term day-and-night rotating shift work poses a barrier to the normalization of alanine transaminase

Abstract: To evaluate the impact of day-and-night rotating shift work (RSW) on liver health, we performed a retrospective analysis of the association between long-term RSW exposure and the normalization of plasma alanine transaminase (ALT) levels over a five-year period. The data from physical examinations, blood tests, abdominal sonographic examinations, personal histories, and occupational records were collected from a cohort of workers in a semiconductor manufacturing company. The sample population was divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…In our study, e-ALT was found among 15.4% of the workers, and this prevalence was similar to that among Japanese male workers in a computer and printer assembly company (16.3%) 10. Lin and Chen reported that the incidence rate of e-ALT was 14.4% among Taiwanese electronic manufacturing workers after 5 years’ follow-up9; they further concluded that night shift work was attributable in the high risk of e-ALT and it hampered the normalisation of ALT 8. Our findings support that night shift work is associated with an increased risk of e-ALT and provide additional evidence concerning dose–response relationships among workers with or without NAFL and of different BMI categories, which have never been reported in previous studies.…”
Section: Discussionsupporting
confidence: 60%
“…In our study, e-ALT was found among 15.4% of the workers, and this prevalence was similar to that among Japanese male workers in a computer and printer assembly company (16.3%) 10. Lin and Chen reported that the incidence rate of e-ALT was 14.4% among Taiwanese electronic manufacturing workers after 5 years’ follow-up9; they further concluded that night shift work was attributable in the high risk of e-ALT and it hampered the normalisation of ALT 8. Our findings support that night shift work is associated with an increased risk of e-ALT and provide additional evidence concerning dose–response relationships among workers with or without NAFL and of different BMI categories, which have never been reported in previous studies.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, it has been speculated that shift work is causally associated with NAFLD (5,35), with population studies demonstrating an increased prevalence of NAFLD among shift workers; however, it is unclear whether this is because of changes in diet, the shift work per se (1,46), or some interaction between them. In the current study, HFD mice had a marked increase in hepatocyte triglyceride and glycogen content.…”
Section: G937 Circadian Disruption Of Metabolismmentioning
confidence: 99%
“…Epidemiological studies suggest that long-term circadian misalignment, such as occurs with shift work, is a risk factor for insulin resistance (13), type 2 diabetes (9), metabolic syndrome (27), obesity (10,16,52,55), hyperlipidemia (7), and nonalcoholic fatty liver disease (NAFLD) (34,35). There are various animal models to mimic human shift work, including altering the timing of food intake, activity, sleep, or light exposure (40).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these data suggest that prolonged CCD and ablation of SRC-2 create a predisposition for HCC. In fact, case studies of shift workers reveal that these individuals are at a greater risk for liver damage and liver cancer than those exposed to normal light schedules (Lin et al, 2014; Lin and Chen, 2015; Echave Llanos and Nash, 1970). Collectively, our data demonstrate that SRC-2 is at the nexus of metabolic and circadian regulation of liver gene programs.…”
Section: Discussionmentioning
confidence: 99%
“…Shift work is also associated with increased metabolic disorders including obesity, hypertriglyceridemia, hypertension, and aberrant hormone homeostasis (Karlsson et al, 2001; Scheer et al, 2009; Kiessling et al, 2010; Parsons et al, 2015). Comorbidities of the metabolic syndrome are often observed in the CCD population, which include type 2 diabetes mellitus, cardiovascular disease, and the most prevalent chronic liver disease in developed countries, non-alcoholic fatty liver disease (NAFLD) (Wang et al, 2011; Lin et al, 2014; Lin and Chen, 2015; Sookoian and Pirola, 2009). The increased incidence of NAFLD that accompanies CCD also creates a predisposition for cirrhosis and hepatocellular carcinoma (HCC) and has even been reported to accelerate aging and increase mortality (Froy, 2013; Kondratova and Kondratov, 2012).…”
mentioning
confidence: 99%